ERN eUROGEN guidelines on the management of anorectal malformations part III: lifelong follow-up and transition of care - Aubert, Ophelia; Irvine, Willemijn F. E.; Aminoff, Dalia; Baauw, Ivo de; Cascio, Salvatore; Cretolle, Célia; Iacobelli, Barbara Daniela; Lacher, Martin; Mantzios, Konstantinos; Miserez, Marc; Sarnacki, Sabine; Schmiedeke, Eberhard; et al. (European journal of pediatric surgery, 2024)
Introduction Anorectal malformations (ARMs) are complex congenital anomalies of the anorectal region, oftentimes also affecting the genitourinary system. Although successful surgical correction can often be achieved in the neonatal period, many children will experience functional problems in the long term. The European Reference Network for rare and complex urogenital conditions (eUROGEN) assembled a panel of experts to address these challenges and develop comprehensive guidelines for the management of ARM. Methods The Dutch Quality Standard for ARM served as the foundation for the development of guidelines applicable on a European level. Literature was searched in Medline, Embase, and Cochrane. The ADAPTE method was utilized to incorporate the newest available evidence. A panel of 15 experts from 7 European countries assessed currency, acceptability, and applicability of recommendations. Recommendations from the Dutch Quality Standard were adapted, adopted, or rejected and recommendations were formed considering the current evidence and/or expert consensus. Results Lifelong follow-up, integration, and transition of care were assessed. A total of eight new studies were identified. The panel adapted 18 recommendations, adopted 6, and developed 6 de novo. Overall, the level of evidence was considered low.Conclusion Successful lifelong follow-up and transition of care require a dedicated team of pediatric and adult specialist and an individually tailored patient-centered approach. This guideline summarizes the best available evidence on follow-up of ARM patients and provides guidance for the development of structured transition programs.
Artikel online veröffentlicht: 19. September 2024
Gesehen am 07.01.2025